Pharmacological Management of Complications of End Stage Renal Disease in Patients on Maintenance Hemodialysis. - K, Justin; S, Savitha; M, Florindo A; S, Manjunath S (Indian Journal of Pharmacy Practice)
End stage renal disease (ESRD) is an important health concern due to the high rates of associated mortality. Complications due to ESRD have been implicated in death or having a significant effect on the patients' quality of life. This study aimed to assess the causes, complications, and the pharmacological management in patients with ESRD who are on maintenance hemodialysis. This prospective observational study included patients visiting the dialysis unit with glomerular filtration rates (GFR) <15 ml/min. Data was collected from case notes, medication charts, dialysis notes and laboratory reports. The complications due to ESRD were classified according to the ICD codes and the management strategies were classified according to the WHO Anatomic Therapeutic Chemical (ATC) code. Among 150 patients enrolled, 112 of them were male patients. The mean age of the study population was 52.51 ± 12.8 years. The most common causes of ESRD were type 2 diabetes mellitus and hypertension. The most common complications associated with ESRD were anemia (93%) and hyperkalemia (92%). Oral iron supplementation and erythropoietin injections were used to manage anemia. Mean hemoglobin levels in patients who received both erythropoietin injection and oral iron, and oral iron only were 8.61 ± 2.16 and 6.3 ± 2.4 respectively. Drugs acting on the alimentary tract (44.8%), cardiovascular system (27.2%) and blood formation (16.8%) were prescribed commonly. Multiple drug use was observed in patients undergoing hemodialysis. Oral iron and erythropoietin injections used together showed improvement in hemoglobin levels as compared to oral iron alone. Patients with co-existing diabetes and hypertension had a higher risk of developing complications with kidney disease.
Keywords: Kidney Disease; End Stage Renal Disease; Hemodialysis